2005
DOI: 10.1002/best.200590184
|View full text |Cite
|
Sign up to set email alerts
|

Fugenlose Betonbrücken mit flexiblen Widerlagern

Abstract: Die fugenlose Bauweise eröffnet dem häufig als massig und plump charakterisierten Beton neue Perspektiven. Dies gilt besonders für Brücken, da sie über einen langen Zeitraum nicht nur störungsfrei funktionieren, sondern auch von Nutzern und Anwohnern als Artefakte akzeptiert werden sollten. Obwohl mittlerweile umfassende Erfahrungen vorliegen, stößt diese Bauweise noch immer auf Skepsis. Entscheidender Einwand ist die Frage nach der sicheren Beherrschung der durch Zwängungen verursachten Risse im Beton. Im ers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 6 publications
0
4
0
4
Order By: Relevance
“…In order to mitigate the aforementioned design issues, England [27] has patented a displacement compensation unit for integral bridges, Horvath [28] has introduced the use of expanded polystyrene and mechanically stabilised backfills to rectify the ratcheting effects, and Hoppe [29] introduced the use of elasticised expanded polystyrene to alleviate interaction effects. Potzl et al [30] tested fullheight abutments with expanded polystyrene layers interjected between the abutment and the soil. However, it was found that the polystyrene exhibits permanent deformations and creeps [31]; therefore, gaps are being created between the abutment and the backfill, which allow the soil to flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to mitigate the aforementioned design issues, England [27] has patented a displacement compensation unit for integral bridges, Horvath [28] has introduced the use of expanded polystyrene and mechanically stabilised backfills to rectify the ratcheting effects, and Hoppe [29] introduced the use of elasticised expanded polystyrene to alleviate interaction effects. Potzl et al [30] tested fullheight abutments with expanded polystyrene layers interjected between the abutment and the soil. However, it was found that the polystyrene exhibits permanent deformations and creeps [31]; therefore, gaps are being created between the abutment and the backfill, which allow the soil to flow.…”
Section: Introductionmentioning
confidence: 99%
“…Potzl et al [30] tested full-height abutments with expanded polystyrene layers interjected between the abutment and the soil. However, it was found that the polystyrene exhibits permanent deformations and creeps [31], therefore gaps are being created between the abutment and the backfill, which allow the soil to flow.…”
Section: Introductionmentioning
confidence: 99%
“…B. [11,12]). Die Intention dieser Maßnahmen ist es einerseits, den Pfahlkopfbereich weicher zu gestalten, und andererseits, den mobilisierten Erddruck hinter der Widerlagerwand zu reduzieren.…”
Section: Einfluss Von Weicheinlagen 341 Allgemeinesunclassified
“…14 In the latter case, the aim is to minimize its in-service loading. Potzl et al 15 have also employed the use of EPS in full height abutments. It ap pears that the in-service bridge-abutment-backfill interaction has attracted most of the current research.…”
mentioning
confidence: 98%